Biochemistry Concept Level of Difficulty Profile of Prospective Biology Teachers’ Perception - Hafnati Rahmatan (Proceedings of AICS - Social Sciences, 2016)
This descriptive study deals with the prospective teachers’ difficulties in understanding the biochemistry concepts to obtain a figure of biochemistry difficulty profile. The subjects of this research are 42 2nd semester biology students in at LPTK in Aceh Province. The data needed for this study are collected by using an open and closed questionnaire referring to the Likert scale. The data are statistically processed. The results showed that the most difficult biochemistry topics include the topics on the catabolism of carbohydrates (27.3%), catabolism of lipids (16.8%), and catabolism of protein (14.5%). The difficulties in mastering the concepts are sought to be due to their using a lot of chemical formulas and chain reactions that hindered the students to fully understand them. These concepts will be easier to understand and attractive by using computer technology. The results show that biochemistry is important for the prospective teachers. In terms of this, it is highly recommended to prepare good material, learning, and authentic assessment that provide challenges and improve students’ capabilities that can be applied in real life situations. Besides, it is important to do continuous and periodic assessment on this matter